Characterization of farnesyl diphosphate farnesyl transferase 1 (FDFT1) expression in cancer - Tuzmen, Sukru; Hostetter, Galen; Watanabe, Aprill; Ekmekci, Cumhur; Carrigan, Patricia E.; Shechter, Ishaiahu; Mousses, Spyro (Future Medicine Ltd, 2019)
Aim:To help characterize theFDFT1 gene and protein expression in cancer.Cholesterol represents an important structural component of lipid rafts. These specializations can be involved in pathways stimulating cell growth, survival and other processes active in cancer. This cellular compartment can be expanded by acquisition of cholesterol from the circulation or by its synthesis in a metabolic pathway regulated by the FDFT1 enzyme. Given the critical role this might play in carcinogenesis and in the behavior of cancers, we have examined the level of this enzyme in various types of human cancer. Our demonstration of elevated levels of FDFT1 mRNA and protein in some tumors relative to surrounding normal tissue identifies this as a possible biomarker for disease development and progression, and as a potential new target for the treatment of cancer.
Keywords: cancer; cholesterol; FDFT1; gene expression; immunohistochemistry; lipidrafts; microdomains; plasma membrane; qPCR; TMA